Augmented catalytic effect of nano‐bi‐transition metal ferrite NiZnFe2O4 for nano‐nitrotriazolone thermolysis. (13th June 2022) - Dave, Pragnesh N.; Thakkar, Riddhi; Sirach, Ruksana
Abstract : The present research aims to study the thermolysis behavior of nano‐nitrotriazolone (nNTO) with and with catalyst bi‐transition metal ferrite (NiZnFe2 O4 ‐NZF). Synthesized NTO via consecutive reaction method was modified to nanosize by using solvent–antisolvent method, while co‐precipitation method was used for the preparation of ferrite. Their physico‐chemical characteristics have been investigated in detail by using X‐ray diffraction (XRD), field emission gun scanning electron microscope (FEG‐SEM), Fourier transform infrared (FTIR), Raman, and ultraviolet–visible (UV–vis) analytical techniques. The catalytic performance was studied briefly using simultaneous thermal analyses. The average crystalline size of NZF is found between 12 and 25 nm, while NTO and nNTO are found between 15 and 40 nm. The nNTO derived from NTO showed higher crystallinity and less agglomeration, while NZF has nanoparticles with polyhedral shape. The thermal results are depicted that this catalyst worked superior to enhance thermolysis of nNTO than its mixture with NTO and it was evaluated by the various kinetic model. The kinetic mean values revealed that nNTO + NZF activation energy decreased in the range of 100–150 kJ mol −1 . According to the obtained results, such kind of catalyst has been used for the preparations of explosive energetic formulations that are widely applicable in rocketry development. Abstract : Nitrotriazolone's thermal decomposition was investigated using simultaneous thermal analyses in the presence of NiZnFe2 O4 catalyst. The results were found that this NiZnFe2 O4 catalyst functioned better to augment thermolysis of nano‐NTO than its mixture with NTO and it was further assessed by the various kinetic model.